The Influence Of Swallowing Exercise On The Ability To Swallow In Stroke Patients With Dysphagia - Iskandar Markus Sembiring (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Signs and symptoms that can be seen in stroke patients are difficulty chewing and swallowing food, coughing, and food often getting stuck in the throat. This event is often called dysphagia. Stroke patients who experience dysphagia amount to 37% to 78%. The effects of dysphagia cause several disease complications that aggravate the patient's condition such as: malnutrition, dehydration, pneumonia, and death. The purpose of this study was to determine the effect of swallowing exercises on the swallowing ability of stroke patients with dysphagia at Grandmed Lubuk Pakam Hospital in 2023. The research method uses a quasi-experimental (one group pretest-posttest design) with 20 respondents. Consecutive sampling is a technique used in sampling. The intervention given to each respondent was in the form of swallowing exercises for 10 sessions. Initial screening for dysphagia was carried out using an observation sheet from the nursing bedside swallowing screening, while the Mann Assessment of Swallowing Ability (MASA) instrument was used to assess the level of ability to swallow. The results of this study indicated that the average mean swallowing ability increased after being given the intervention and found differences in swallowing ability before and after the intervention was given with a value of p = 0.000. The conclusion is that the ability to swallow in stroke patients with dysphagia can be overcome by doing swallowing exercises regularly. It is expected that health workers (nurses) are active in teaching or directing patients who experience dysphagia so that complications do not occur in stroke patients.